THE EFFECTIVENESS OF 3D HUMAN ANATOMY APPLICATION ON PHYSICAL EDUCATION STUDENTS OF MULAWARMAN UNIVERSITY - Gyta Krisdiana Cahyaningrum; Jupri; Didik Cahyono (Program Studi Pendidikan Jasmani, 2023)
The unavailability of learning media that supports the human anatomy course in the form of teaching aids, as well as the absence of the application of digital-based learning methods, so that students can only listen, waiting their turn to be able to observe the teaching aids more closely so they can be seen more clearly. Data collection consists of questionnaires distributed via Google Form and the data is processed using quantitative descriptive analysis techniques. The subjects in this study were 68 physical education students in semester 1 of 2022 who participated in an analysis of the use of digital-based learning media using 3D human anatomy application during the teaching and learning process in the Unmul physical education classroom. The results of data analysis from the use of digital-based learning media using 3D human anatomy application can foster students' democratic attitudes, encourage more active and independent learning, increase motivation to learn during lectures and understand learning effectively and efficiently, and enable learning according to the place and time students are interested in. The obstacles often experienced in digital-based learning are using 3D human anatomy applications and an unstable internet network.